Enhancement in Photovoltaic Properties of N, N‐diethylaniline based Donor Materials by Bridging Core Modifications for Efficient Solar Cells. Issue 17 (4th May 2020) - Hussain, Riaz; Khan, Muhammad Usman; Mehboob, Muhammad Yasir; Khalid, Muhammad; Iqbal, Javed; Ayub, Khurshid; Adnan, Muhammad; Ahmed, Mahmood; Atiq, Kainat; Mahmood, Khalid
Abstract: The increasing demand of energy expedited the development of efficient photovoltaic materials.Herein, five push‐pull donor materials (D1 ‐D5 ) having N, N ‐diethylaniline as donor moiety and rhodanine‐3‐acetic as acceptor group are designed to be used as donor molecules in organic solar cells (OSCs). The bridging core modification of recently synthesized MR3 molecule (reference R ) has been made with different π‐spacers namely thiazole (B1 ), thieno[3, 2‐b]thiophene (B2 ), thiazolo[5, 4‐d] thiazole (B3 ), 2‐(thiophen‐2‐yl)thiophene (B4 ) and 5‐(thiazol‐5yl)thiazole (B5 ). The structure–property relationship is studied and influence of bridging core modifications on photovoltaic, photophysical and electronic properties of D1‐D5 are calculated and compared with reference R .The DFT and TDDFT calculations have been performed for the estimation of frontier molecular orbital (FMO) analysis, density of states (DOS) graphs, reorganization energies of electron and hole, open circuit voltage, photophysical characteristics, transition density matrix (TDM) surfaces and charge transfer analysis.Designed molecules exhibit better and comparable optoelectronic properties than synthesized reference molecules. Among all investigated molecules, D5 is proven as best candidate for OSCs application due to its promising photovoltaic properties including lowest band gap (2.24 eV), small electron mobility (λe =0.0056 eV), small hole mobility (λh =0.0046 eV), low binding energy (Eb =0.21 eV), highest λmax values 610.76 nm (in gas) 670.22 nm (in acetonitrile) and high open circuit voltage (Voc =1.17 V) with respect to HOMOdonor –LUMOPC61BM . This theoretical framework demonstrates that bridging core modification is a simple and effective alternative strategy to achieve the desirable optoelectronic properties. Furthermore, conceptualized molecules are superior and thus are recommended to experimentalist for out‐looking future developments of highly efficient solar cells. Abstract : Five push‐pull donor materials (D1‐D5) having N, N ‐diethylaniline as donor moiety and rhodanine‐3‐acetic as acceptor group are designed to be used as donor molecules in organic solar cells. Various parameters like FMOs, DOS, optical properties, open circuit voltage and charge transfer analysis is carried out by utilizing density function theory at B3LYP/6‐31G(d, p) basis set. All designed molecules show better optoelectronic properties as compared to R. The designed compounds should be targeted for synthesis to develop highly efficient solar cells.